2022
DOI: 10.18231/j.ijcaap.2022.007
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following immunization (AEFI) for Covid vaccines approved by WHO- A short review

Abstract: The world was suffering and People are in great grief due to COVID 19 Pandemic 2020 and 2021 due loss of life, jobs and other related socio-economic issues and now it has been in subsiding mode due to the great weapon COVID vaccine. However omicron is now threatening due to high transmissibility compare to other variants of Corona virus. All of us aware corona Vaccines have been permitted by the regulatory authorities of different countries under emergency situation for restricted use. However by considering R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…An unprecedented mass vaccination effort took place worldwide. The most commonly used vaccine is the BNT162b2 Pfizer–BioNTech mRNA vaccine, which is approved in 123 countries [ 4 ]. Studies showed that fever, fatigue, headache, and injection site pain are among the most common adverse events associated with this vaccine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unprecedented mass vaccination effort took place worldwide. The most commonly used vaccine is the BNT162b2 Pfizer–BioNTech mRNA vaccine, which is approved in 123 countries [ 4 ]. Studies showed that fever, fatigue, headache, and injection site pain are among the most common adverse events associated with this vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that fever, fatigue, headache, and injection site pain are among the most common adverse events associated with this vaccine. Furthermore, serious adverse events include shoulder injury related to vaccine administration, right axillary lymphadenopathy, paroxysmal ventricular arrhythmia, right leg paresthesia, fatigue and headache [ 4 ]. The number of reported vaccine-related adverse events was also unprecedented.…”
Section: Introductionmentioning
confidence: 99%